Lungs damage in Behçet’s disease - R G Goloeva; Z S Alekberova; T V Lapinaa (Научно-практическая ревматология, 2009)
Behçet’s disease (BD) is a systemic vasculitis of unknown origin characterized by ulcerous damage of oral and genital mucosa as well as eyes and skin. Other organs (nervous system, lungs, joints, gastro-intestinal tract) are rarely involved. Damage of vessels of all sizes and types is a feature of this vasculitis. Review of main lung BD manifestations (pulmonary artery aneurisms, arterial and venous thrombosis, parenchymatous lung damage) and own description of a pt with BD with multiple pulmonary aneurisms are presented.